2016
DOI: 10.1016/j.fertnstert.2015.12.138
|View full text |Cite
|
Sign up to set email alerts
|

Women infected with human immunodeficiency virus type 1 have poorer assisted reproduction outcomes: a case-control study

Abstract: In one of the largest studies to pair six factors that influence the results of ART, HIV infection in women was associated with poorer outcomes after ART. These results suggest that women with controlled HIV-1-infection should be counseled not to delay ART in cases of self-insemination failure or other causes of infertility. Fertility preservation by vitrification of oocytes in women whose pregnancy should be delayed may be an important future consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…In a similar line of study, another group did not find any differences in AMH levels and antral follicles count between HIV-1-positive and non-infected women [28]. These authors did not note any differences in ovarian stimulation, duration, total gonadotropins units administered, except for a difference in E 2 levels, but lower pregnancy rates were observed [28], in line with the results we obtained in this work. Except for AMH levels that were reduced in HIV subgroup, no other differences were observed for the number of antral follicles and the concentrations of FSH in relation to controls, which suggests that all groups possess similar ovarian reserve.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a similar line of study, another group did not find any differences in AMH levels and antral follicles count between HIV-1-positive and non-infected women [28]. These authors did not note any differences in ovarian stimulation, duration, total gonadotropins units administered, except for a difference in E 2 levels, but lower pregnancy rates were observed [28], in line with the results we obtained in this work. Except for AMH levels that were reduced in HIV subgroup, no other differences were observed for the number of antral follicles and the concentrations of FSH in relation to controls, which suggests that all groups possess similar ovarian reserve.…”
Section: Discussionsupporting
confidence: 89%
“…The number of clinical pregnancies in HIV-positive women also did not change [13] [27]. In a similar line of study, another group did not find any differences in AMH levels and antral follicles count between HIV-1-positive and non-infected women [28]. These authors did not note any differences in ovarian stimulation, duration, total gonadotropins units administered, except for a difference in E 2 levels, but lower pregnancy rates were observed [28], in line with the results we obtained in this work.…”
Section: Discussionmentioning
confidence: 90%
“…In a women's age-adjusted study in 2005, Terriou et al (22) showed that the total gonadotropin dose, the duration of stimulation, and the cancellation rate were significantly higher, and the clinical pregnancy rate was much lower in the ''women HIV'' group compared with controls. In 2016, in a retrospective case-control study, Stora et al (19) compared 82 couples who were HIV-positive with 82 seronegative couples standardized on several criteria (age of the woman, etiology and type of infertility, the rank and technique of the IVF cycle). In the ''women HIV'' group, implantation rate, clinical pregnancy rate (by transfer and by oocyte retrieval), and live birth rate (by transfer) were significantly lower compared with those of controls.…”
Section: Discussionmentioning
confidence: 99%
“…14 If conception is not achieved within 6 to 12 months, couples should be referred to a specialist for investigation as infertility rates are higher in the seropositive population with lower rates of implantation (10% vs 21%), pregnancy (12% vs 32%) and live-births (7% vs 19%) compared to uninfected controls. 15 Sperm washing followed by intrauterine insemination (IUI), in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) is considered safe, with a recent meta-analysis summarizing more than 40 trials in assisted reproductive cycles revealed no documented cases of HIV transmission. 16 Regardless of method of conception, it is recommended that individuals living with HIV initiate cART and achieve viral suppression prior to pregnancy.…”
Section: Pregnancy Planning Considerationsmentioning
confidence: 99%